Weighing options: empiric antibiotic use and stewardship opportunities in critically ill patients with community-acquired pneumonia - Nalea Trujillo; Calvin Diep; David Ha; Ariadna Garcia; Marisa Holubar (Antimicrobial Stewardship & Healthcare Epidemiology)
In this retrospective study, critically ill patients with community-acquired pneumonia frequently received empiric anti-methicillin-resistant Staphylococcus aureus (MRSA) and antipseudomonal antibiotics despite having few or no guidelines-endorsed risk factors. De-escalation of anti-MRSA therapy was quicker, likely aided by MRSA polymerase chain reaction assays.